Methodology to Specify Software Requirements in Assessment System for Decommission of Nuclear Facilities - Sang Song, Hae; Jeong, Kwan-Seong; Hyun, Dongjun; Kim, Geun-Ho; Choi, Byeong-Seon; Moon, Jeikwon (Asian Journal of Chemistry, 2013)
This paper deals with a methodology to specify software requirements as well as the top level requirements of the decommissioning assessment system of nuclear facilities. It then surveys related technologies required to build the system. Specifically the two major parts of the system include the assessment technology for radiation exposure to both the workers and the dismantling equipment and the process simulation of physical dismantling jobs such as moving, cutting and transporting. Also important is analyzing the 3Dimentional interference between physical objects in the course of the jobs. Remote handling equipment to reduce the radiation exposure of workers is also considered. A trade-off study of many alternative processes can be supported using the system under consideration. This paper is expected to contribute to the development of requirements of the decommissioning process assessment system.